AB0876 THE BENEFIT AND SAFETY OF DIACEREIN IN AGED AND OBESE PATIENTS WITH SYMPTOMATIC KNEE OSTEOARTHRITIS: DATA FROM THE DISSCO CLINICAL STUDY. (2nd June 2020) - Pelletier, J. P.; Raynauld, J. P.; Dorais, M.; Paiement, P.; Martel-Pelletier, J.
Abstract : Background: The DISSCO trial (6-month international, multicentre, double-blind, randomised study on the effect of diacerein vs celecoxib in symptomatic knee osteoarthritis [OA] patients) showed that diacerein had comparable efficacy to celecoxib at reducing the level of pain (WOMAC pain). Objectives: To assess the effect of age, body mass index (BMI), and gender on the efficacy/safety profile of diacerein following 6 months of treatment. Methods: Of the patients (n=380) that were randomised, 186 received treatment with 50 mg diacerein once daily for the first month and twice daily thereafter. This study was done on the intent-to-treat population (n=183). Efficacy outcome assessments which included absolute change in WOMAC pain (score 0-50) and function (score 0-170), and VAS (score 0-10) were analysed following stratification based on age (< 65 vs ≥ 65 years old) and BMI (< 30 vs ≥ 30 kg/m 2 ) at time of randomisation. Treatment effects on continuous efficacy outcomes were performed using covariance analysis (ANCOVA). For gastrointestinal (GI) safety outcomes, the adverse events (AEs), including diarrhoea, soft faeces, abdominal pain and dyspepsia, and the time-to-onset from baseline were stratified according to age of patients at randomisation. Treatment-related GI AEs were also assessed according to the gender. The independent variables were treatment, stratification variable, interaction between both, and the outcome measure at baseline. Comparisons between groups were carried out using Chi-square. Results: No significant differences were found between the two age groups (<65 years old [n=105], ≥65 years old [n=78]) in the level of reduction in WOMAC pain (-10.3 ± 1.1, -8.6 ± 1.3, respectively; p=0.30), VAS (-2.3 ± 0.2, -2.2 ± 0.3, p=0.73) or improved physical function (-29.7 ± 3.7, -22.1 ± 4.2, p=0.18). The reported incidences of treatment-related GI AEs were also similar between the two age groups; more specifically for diarrhoea, incidence for patients <65 years old [n=12] 11.3% and for those ≥65 years old [n=7] 8.8% (p=0.63) with a mean time-to-onset (day 43 ± 49, 61 ±51, respectively; p=0.11). Moreover, gender had no influence on treatment-related GI AEs (p=0.42). In regard to treatment response of obese (n=101) vs. non-obese (n=82) patients in terms of pain reduction (WOMAC: -10.1 ± 1.2, -9.1 ± 1.1, respectively; p=0.58; VAS: -2.6 ± 0.3, -2.0 ± 0.3; p=0.15), or improved WOMAC physical function (-29.8 ± 4.2, -23.5 ± 3.8; p=0.26), there were also no significant differences. Conclusion: In symptomatic knee OA patients, the level of effectiveness and safety profile of treatment with diacerein were found not to be influenced by age, BMI or gender. Disclosure of Interests: Jean-Pierre Pelletier Shareholder of: ArthroLab Inc., Grant/research support from: TRB Chemedica, Speakers bureau: TRB Chemedica and Mylan, Jean-Pierre Raynauld Consultant of: ArthroLab Inc., Marc Dorais Consultant of: ArthroLab Inc., Patrice Paiement Employee of: ArthroLab Inc., Johanne Martel-Pelletier Shareholder of: ArthroLab Inc., Grant/research support from: TRB Chemedica